Marketing communication of railway passenger carriers on the social network Facebook in times of SARS-CoV-2 epidemic - Chocholáč, Jan; Becková, Helena; Šolcová, Lenka (Univerzita Tomáše Bati ve Zlíně, 2022)
The SARS-CoV-2 epidemic became a challenge for many companies and marketers because it was necessary to revise marketing communication tactics and not lose contact and relationship with customers/consumers even in times of epidemic related restrictions. This paper focuses on marketing communication of railway passenger carriers on the social network Facebook in times of SARS-CoV-2 epidemic. The aim of this paper is to analyse Facebook marketing communication of the Czech Railways, RegioJet, and Leo Express in 2020 and compare the results with the 2019 study. This paper is prepared as a comparative study with the paper of Chocholáč and Becková (2020). The qualitative content analysis and comparative analysis was used for analysing the profiles of selected passenger railway carriers on the social network Facebook. The results of the analysis clearly show that the SARS-CoV-2 epidemic affected railway passenger carriers' marketing communication on Facebook on several levels. The first significant level was the content of individual posts, which were logically significantly influenced by the epidemiological situation. The second level was the number of published posts, with some carriers (RegioJet and Leo Express) publishing significantly fewer posts in 2020 than in 2019. Czech Railways tried to maintain contact with customers/consumers as much as possible even in epidemically difficult times and increased the number of published posts. The paper's main contribution is a comprehensive analysis of marketing communication of selected railway passenger carriers on the social network Facebook and an assessment of the impact of the SARS-CoV-2 epidemic.
Marketingová komunikace železničních osobních dopravců na sociální síti Facebook v době epidemie SARS-CoV-2
Keywords: online marketing; social media marketing; social network marketing; Czech Railways; RegioJet; Leo Express; online marketing; marketing na sociálních médiích; marketing na sociálních sítích; České dráhy; RegioJet; Leo Express